2009
DOI: 10.1007/s11239-009-0422-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, clinical correlates and treatment of permanent atrial fibrillation among the elderly: insights from the first prospective population-based study in rural Greece

Abstract: To investigate the prevalence of permanent atrial fibrillation (AF), its clinical associated conditions and treatment status in the elderly population in rural Greece. 720 people (46.1% males) older than 65 years (mean age: 72.5 +/- 5.7 years) living in four villages in rural Greece were screened with an electrocardiogram (response rate: 90.5%) for the presence of permanent AF. They underwent a physical examination, including blood pressure (BP) measurement, and body mass index (BMI) calculation, in addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…Overall, AF was found to be higher among those with advanced age (19-22, 24-26, 28-30), male gender (19)(20)(21)(22)30), hypertension (19,21,24,28,31), diabetes (19,24,28), prior myocardial infarction (16,21,26,28,30), prior stroke (21,24,29), obesity (26,29), hyperlipidemia/hypercholesterolemia (19,29,30), alcohol consumption (16,26,28), and heart failure (24). Furthermore, ECG and echocardiographic fi ndings of left ventricular hypertrophy (22,26,28,30), low left ventricular ejection fraction (28), left bundle branch block (16), left atrial diameter (30), peak early rapid fi lling wave velocity (30), myocardial ischemia (21), and ventricular premature beats (21) were found to be associated with AF. Only six studies (19,24,26,(28)(29)…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Overall, AF was found to be higher among those with advanced age (19-22, 24-26, 28-30), male gender (19)(20)(21)(22)30), hypertension (19,21,24,28,31), diabetes (19,24,28), prior myocardial infarction (16,21,26,28,30), prior stroke (21,24,29), obesity (26,29), hyperlipidemia/hypercholesterolemia (19,29,30), alcohol consumption (16,26,28), and heart failure (24). Furthermore, ECG and echocardiographic fi ndings of left ventricular hypertrophy (22,26,28,30), low left ventricular ejection fraction (28), left bundle branch block (16), left atrial diameter (30), peak early rapid fi lling wave velocity (30), myocardial ischemia (21), and ventricular premature beats (21) were found to be associated with AF. Only six studies (19,24,26,(28)(29)…”
Section: Resultsmentioning
confidence: 96%
“…We noted signifi cant associations between rural AF and increasing age (19-22, 24-26, 28-30). Male gender (19)(20)(21)(22)30), hypertension (19,21,24,28,31), diabetes (19,24,28), prior myocardial ischemia/infarction (16,21,26,28,30), alcohol consumption (16,26,28), prior stroke (21,24,29), and obesity (26,29) were also associated with AF. What is apparent from our review is that none of the studies reported all the risk factors or comorbidities that may be associated with AF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A cross-sectional study of 1178 patients with AF attending 12 emergency departments (EDs) in Spain found that 89% of the patients not taking anticoagulants had indications for anticoagulation, with 63% of these patients having two or more risk factors (19). The pattern of underuse of warfarin recurs in Switzerland (20), Japan (21) and Greece (22).…”
Section: Anticoagulants and The Underuse Of Warfarinmentioning
confidence: 99%